Effects of flaxseed extract on the viability of stem cells from human extracted deciduous teeth (SHED) - Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Nordin, Nursazwi; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari; Lestari, Widya; Ahmad, Azlina; Thirumulu Ponnuraj, Kannan (Frontiers Media, 2016)
Various beneficial pharmacological effects have been ascribed to the biologically active components of flaxseed extracts; such as lignans, flavonoids and omega 3 compounds. Studies have shown that flaxseed extract promotes bone health and possibly able to induce bone regeneration process. Hence, our study was initiated to ascertain the effects of flaxseed extract in the osteogenic differentiation potential of stem cells from human exfoliated deciduous teeth (SHED). SHED; a mesenchymal stem cells (MSC), have been considered as alternative sources of adult stem cells in tissue engineering because of their potential to differentiate into multiple cell lineages including osteoblast. Thus the aim of this study was to investigate the effects of flaxseed (ethanol extract) on SHED in terms of cell viability and morphology. Whole flaxseeds were ground and extracted using 99.8% ethanol in a Soxhlet chamber. Ethanol (99.8%) was used for extraction because it is safe to the environment and less toxic compare to other solvent. The solvent containing the extract was collected and evaporated using rotary evaporator under reduced pressure at 60°C. The concentrated extract was then frozen and freeze-dried for 30 minutes to remove water residue. The crude extract were kept in a closed container and stored at 4°C until further use. The flaxseed extracts was dissolved in DMSO and filter sterilized with 0.22 um PES syringe filter. The stock solution for the plant extracts were 1.6 g/ml. MTT assay (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) was carried out to determine the cell viability of SHED after treatment with the flaxseed extracts. SHED (AllCells, USA) was previously cultured and maintained in alpha-MEM (GIBCO, USA) containing 10% FBS (GIBCO, USA) and 0.5% penicillin/streptomycin (GIBCO, USA) until confluent. Cells were then trypsinised and subjected for further analysis. SHED at a density of 1000 cells/well were seeded in 96-well plates and incubated for 24 hours. Then 100 μL fresh media containing extracts at a final concentration of 4, 8, 10, 12, 14, 16 mg/ml were added and incubated for another 72 hours. The media was discarded and 50 μL of MTT dissolved in alpha-MEM was added to each well at a final concentration of 0.5 mg/ml and incubated for further 4 hours. The supernatant was discarded and the formazan blue crystals formed were dissolved in 200 μL of DMSO. The complete media was used as a control. All incubations were performed in a CO2 incubator (5%) at 37 °C. The percentage of cell viability was calculated using the following equation: Cell viability (%) = (A) test/ (A) control x 100; where (A) test is the absorbance of test sample and (A) control is the absorbance of the control sample. The morphology of the cells after treatment with different concentrations of crude extract was also observed using inverted microscope (Nikon). Overall, the effects of flaxseed extract on SHED were observed to be dose-dependent, where higher concentration of the extract resulted in lower cell viability (Figure 1). It was also observed that SHED treated with 4 and 8 mg/ml of extract produced cell viability higher than the control. On the other hand, SHED treated with 16 mg/ml of extract showed a significant cell death after 72 hours of incubation. The concentration of the extracts required to inhibit 25 and 50 percent of cell viability were 9.15 mg/ml and 10.56 mg/ml respectively. Statistical analysis showed that there is a significant difference between IC50 and IC25 (p < 0.05). The morphology of SHED started to change as the concentration of flaxseed increased. The untreated cells maintained its elongated and fibroblast-like shape. The cells appeared healthy in cells treated with 4 mg/ml of extract while increase of granulation in the cytoplasm of the cells followed by vacuolation were observed in cells treated with higher concentration of extracts (> 8mg/ml). The cell viability assay as well as morphological observation indicated that flaxseed extract was not toxic to the cells at concentration up to 8 mg/ml as demonstrated in the current study. SHED treated with 4 mg/ml of flaxseed extract gave highest cell viability with no morphological changes; hence this concentration will be used for further analysis in the current study. Flaxseed contains phenolic acids, flavonoids and other phenylopropanoids compounds that are known to possess anti-oxidant properties. Therefore it could be suggested that the cell viability of SHED may due to the presence of phenolic compound found in the extract indicating the potential of this extract to be used further in research relating to tissue engineering involving stem cells.